Health-related quality of life and associated factors among Onchocerciasis patients in southeast Nigeria: A cross-sectional comparative study. - Adah E Otache; Ifeyinwa L Ezenwosu; Edmund N Ossai; Elias C Aniwada; Emmanuel A Nwobi; Benjamin Sc Uzochukwu (Public Library of Science (PLoS), 2022)
Introduction Onchocerciasis, a neglected tropical disease of public health importance, causes chronic morbidity and severe disability that may impact on health-related quality of life (HRQoL) of the infected people. This study assessed the HRQoL and associated factors among onchocerciasis patients in southeast Nigeria. Methods This was a community-based cross-sectional comparative study. Using a multistage sampling technique, 340 onchocerciasis patients were selected and matched for age and gender with the healthy population in the same neighbourhood. The respondents were interviewed using the short-form-36 (SF-36) questionnaire to determine their HRQoL. WHO Disability Assessment Schedule 2.0 tool (WHODAS 2.0) was used to assess disability in persons with onchocerciasis. Means were compared with independent student t-test while Chi-square test was used to compare proportions. Also, correlation analysis and logistic regression were used in the analyses. Results A significantly lower proportion of people living with onchocerciasis had a good quality of life when compared with the healthy subjects (69.4% vs 93.5%, p<0.001). Also, an inverse relationship was seen between disability and quality of life in the onchocerciasis group (r = -0.647, p<0.001). Predictors of poor quality of life among respondents with onchocerciasis were: respondents aged ≥48 years (AOR = 2.5, 95% CI: 1.4-5.0), those with some disability associated with onchocerciasis (AOR = 3.33, 95%CI: 1.4-5.0) and respondents who perceived themselves as a burden to people (AOR = 10, 95%CI: 2.5-20). Conclusion Onchocerciasis impacted negatively on HRQoL of persons with onchocerciasis when compared with the healthy population. The quality of life of persons affected with onchocerciasis reduces with increasing disability. There is the need to increase community awareness on onchocerciasis to ensure early diagnosis and prompt treatment as this will reduce disability among those affected with the disease thus enhancing their HRQoL.